Independensi: Perjalanan Mencari Titik Temu Antara Profesi dan Bisnis Audit - Surya Rahardja (AKSES: Jurnal Ekonomi dan Bisnis, 2007)
Breaching of a company’s independency causes Enron, World Com and almost all auditing scandals. Nowadays, public accounting offices are required not just to be professional but also participate and compete as a company in the industry of auditing services. Independency is getting compromised due to both profession and business interests abound. Based on literature studies, this article tries to discuss both facets of auditing as a business and a profession, the contradiction of those two facets, and the steps that need to be taken for the proper solution. Keywords: independency, auditing, non-auditing services